The Lung Elastin Matrix Undergoes Rapid Degradation Upon Adult Loss of Hox5 Function - Li, Mu-Hang; Marty-Santos, Leilani M.; van Ginkel, Paul R.; McDermott, Aubrey E.; Rasky, Andrew J.; Lukacs, Nicholas W.; Wellik, Deneen M. (Frontiers in Cell and Developmental Biology, 2021)
Hox genes encode transcription factors that are critical for embryonic skeletal patterning and organogenesis. The Hoxa5, Hoxb5 and Hoxc5 paralogs are expressed in the lung mesenchyme and function redundantly during embryonic lung development. Conditional loss of function of these genes during early postnatal stages leads to severe defects in alveologenesis, specifically in the generation of the elastin network, and animals display bronchopulmonary dysplasia (BPD) or BPD-like phenotype. Here we show the surprising results that mesenchyme-specific loss of Hox5 function at adult stages leads to rapid disruption of the mature elastin matrix, alveolar enlargement, and an emphysema-like phenotype. As the elastin matrix of the lung is considered highly stable, adult disruption of the matrix was not predicted. Just two weeks after deletion, adult Hox5 mutant animals show significant increases in alveolar space and changes in pulmonary function, including reduced elastance and increased compliance. Examination of the extracellular matrix (ECM) of adult Tbx4rtTA;TetOCre;Hox5afafbbcc lungs demonstrate a disruption of the elastin network although the underlying fibronectin, interstitial collagen and basement membrane appear unaffected. An influx of macrophages and increased matrix metalloproteinase 12 (MMP12) were observed in the distal lung three days after Hox5 deletion. In culture, fibroblasts from Hox5 mutant lungs exhibit reduced adhesion. These findings establish a novel role for Hox5 transcription factors as critical regulators of lung fibroblasts at adult homeostasis.